Cuproptosis‑related Gene CDKN2D is Linked to Prognosis in Esophageal Cancer - Xu, Xingnong; Ma , Lei; Liu, Shichao (ENT Updates, 2025)
Cuproptosis, a novel type of regulated cell death, is controlled through protein fatty acylation and has been linked to mitochondrial metabolic processes. Nonetheless, continued research efforts are essential to determine how CDKN2D (Cyclin-dependent kinase inhibitor 2D), a gene associated with cuproptosis, influences the tumor immune microenvironment and progression of esophageal cancer (EC). Gene expression levels of CDKN2D in EC and matched normal tissues were assessed using data from The Cancer Genome Atlas (TCGA). To confirm these findings, we conducted validation analyses utilizing datasets from the Gene Expression Omnibus (GEO) and the Human Protein Atlas (HPA). To ascertain if CDKN2D expression levels were associated with clinical outcomes, we conducted a multivariable regression analysis supplemented by Kaplan-Meier survival estimates. The protein-protein interaction network related to CDKN2D was created using the STRING database (Search Tool for the Retrieval of Interacting Genes/Proteins). To characterize the immunological relevance of CDKN2D in EC, we performed comprehensive bioinformatic analyses to assess its correlation with tumor-infiltrating immune cells. Three complementary computational approaches-Gene Ontology (GO) functional annotation, conventional GSEA, and ssGSEA (single-sample GSEA) were integrated to evaluate the immunomodulatory potential of CDKN2D in EC. Transcript abundance level of the CDKN2D in EC samples is considerably higher than in normal tissue samples. Analyses involving both single variables and multiple variables indicate that there is no significant statistical difference in overall survival (OS) between EC patients with high CDKN2D expression and those with low CDKN2D expression (p > 0.05). Cyclin-dependent kinase 4/6 (CDK4/6) is a critical protein that interacts with the CDKN2D gene, and ECs with high CDKN2D expression are bound to a considerable volume of infiltrating immunocytes. Elevated CDKN2D expression in EC correlated with disease progression and modified immune infiltration patterns.